2015
DOI: 10.1186/s12912-015-0116-4
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about dementia in South Korean nursing students: a cross-sectional survey

Abstract: BackgroundThe number of individuals with dementia is increasing substantially due to South Korea’s rapidly aging society. Undergraduate nursing students need to have adequate knowledge about dementia to deliver appropriate nursing services. The purpose of this study was to assess the knowledge about dementia among undergraduate nursing students.MethodsA total of 148 students ranging from freshmen to seniors at a nursing university participated in this study. Data were collected through self-reports using 12-it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
28
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 19 publications
9
28
1
Order By: Relevance
“…Nursing students have less clinical experience, so it is considered that they have less knowledge and confidence to interact with people with dementia and aged people before attending the dementia supporter training program. Previous study also showed that higher level of knowledge about dementia was also associated with experiences in education on dementia [ 21 ]. From this finding, it is hypothesized that nursing students acquire much educational benefits of dementia after the dementia supporter training program.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Nursing students have less clinical experience, so it is considered that they have less knowledge and confidence to interact with people with dementia and aged people before attending the dementia supporter training program. Previous study also showed that higher level of knowledge about dementia was also associated with experiences in education on dementia [ 21 ]. From this finding, it is hypothesized that nursing students acquire much educational benefits of dementia after the dementia supporter training program.…”
Section: Introductionmentioning
confidence: 87%
“…On the other hand, nursing students have had fewer opportunities to engage in such activities. Previous studies have shown that clinical experience for nursing students led much knowledge and improved attitudes toward people with Alzheimer’s disease [ 19 ], toward people with dementia [ 20 ], and higher level of knowledge about dementia was associated with previous experience in caring for people with dementia [ 21 ]. Thus, the clinical experience is an important factor for knowledge and attitude toward people with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…First, students, and especially those learning in the healthcare disciplines, will become the future professionals providing care to persons with dementia and their family members. Accordingly, a myriad of studies assessed knowledge and attitudes towards AD among nursing students (Eccleston et al, 2015;Kimzey et al, 2016;Mitchell et al, 2017;Scerri and Scerri, 2013;Shin et al, 2015), dental hygiene students (Isobe et al, 2018), and medical and pharmacy students (Gilmartin-Thomas et al, 2018). Second, as the number of persons with AD continues to rise (Prince et al, 2016), increasing numbers of young people will be interacting with these older adults as grandchildren and will most likely become family caregivers of persons with the disease (Celdran et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…More than ten years ago, dementia was identified as one of four gerontological public health problems in the elderly in Croatia (Perko, Tomek-Roksandić, Mihok, Puljak, Radašević, Tomić & Čulig, 2005), mostly because of the significant increase in the number of patients suffering from the disease (Gilić, Perinčić & Kovač, 2008). Because of demographic changes, this trend can be seen in most European countries, for example, in Germany (Doblhammer, Fink & Fritze, 2015;Ziegler & Doblhammer, 2009), but also in China and sub-Saharan African regions (Wortmann, 2014), as well as Australia (McCabe, You & Tatangelo, 2016) and South Korea (Shin, Seo, Kim, Kim & Lee, 2015). Dementia affects not only patients, but also families and caregivers.…”
Section: Introductionmentioning
confidence: 99%